Enhanced Recovery after Cardiac Surgery: A Narrative Review - Amarja Nagre; Guriqbal Singh (Journal of the Practice of Cardiovascular Sciences)
Enhanced recovery after cardiac surgery (ERACS) is an evidence-based multidisciplinary, patient-centered, and protocolized program with a primary objective of minimizing the physiological disturbances and the stress response associated with surgery, expediting the recovery of the patient undergoing cardiac surgery with the efficient use of healthcare resources. ERACS includes preoperative optimization, liberal fasting guidelines such as the consumption of carbohydrate drink before surgery, goal-directed fluid therapy, minimally invasive cardiac surgery, fast-tracking extubation, lung protective ventilation, multimodal and opioid sparing analgesia, optimum temperature management, avoidance of postoperative nausea and vomiting, primordial removal of invasive catheters, and early mobilization. The implementation of strategies of ERACS requires coordinated and robust team efforts involving cardiac surgeons, cardiac anesthesiologists, and hospital staff. This structured approach to the perioperative care abbreviates hospital stay and improves the clinical outcomes.